لعبة Typed Game لترقية مهارة كتابة اللغة العربية - Thohir, Muhammad; Rachmawati, Yuanita; Maulida, Citra Puspita; Alkhindi, Muhammad Umar Zaid (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
Arabic is an important language to learn, so we will more easily understand the contents of the Qur'an. To get students' ability to learn Arabic, learning methods are needed that are relevant to their abilities so that they feel happy to learn it. Such as: dictation or imla' method, direct method, hiwar, memorization and so on. A teacher should use good, varied and fun methods and make students active and proficient in the language, especially in writing Arabic. One of the new methods that are considered interesting in learning Arabic is the educative method in learning Arabic, one of the interesting educative methods in learning Arabic is the "Typed Game". Using this method can help students to increase their Arabic vocabulary and can help a teacher to more easily guide students to write Arabic well and correctly, then with the Arabic vocabulary students can learn to make a sentence so that they can improve their skills. student writing. This study aims to determine the application of the Typed Game game in improving students' writing skills in learning Arabic. In essence, writing is a means of communicating with language between people and others who are not limited by time and place. In this case, a teacher teaches Arabic writing with muwajjah (guided). This stage is the initial stage of students in writing vocabulary, where the teacher helps and guides students to write Arabic vocabulary with proper and correct writing. The method used for data collection is observation, interview, questionnaire, test test by taking 43 students of class VIII as the sample. To be able to conclude the desired result, the T test formula (T test) is used. N=43 tt 1%= 2,704 5%=2,21 t0 = 13, 14, this indicates the application of Typed Game to improve students' writing skills.